Prevalencia de sarcosporidiosis sarcocystis spp por inspección en bovinos sacrificados en el camal municipal de el cantón Arenillas - Salgado Feijóo, Jorge Stalin (2009)
The present investigation took place at the municipal slaughter house in the town of Arenillas. The investigation was conducted from January 23rd to April 17th of 2008, with the purpose of determining by means of microscopic inspection if the livestock at the municipal slaughterhouse were infected with Sarcosporidiosis bovina. I suggested the following objectives in order to complete the investigation. First, to determine the prevalence of Sarcosporidiosis bovina at the municipal slaughterhouse of Arenillas. Second, to identify a relation if any between the disease and livestock’s sex, race and age. To carry out this work inspected 415 slaughtered animals during a space of 62 days. The animals examined were from several different towns including Chacras, Palmales, and Arenillas among others. The obtained results determined that Sarcosporidiosis bovina was not present in any of the specimen examined at the municipal slaughterhouse of Arenillas.